Financial stability, economic growth and sustainable development - Baudry, Marc, 1971-; Bukowski, Sławomir; Lament, Marzanna Barbara (Routledge, 2024)
Following multiple global crises, there is an urgent need to review our economic and financial paradigms to improve outcomes for the three pillars of sustainable development: economic, social, and environmental. In response, various strands of new economic thinking have emerged such as degrowth, the collaborative economy, solidarity economy, sharing economy and social entrepreneurship. This book explores the various economic and financial dimensions of sustainable development drawing on new and existing theories. This comprehensive book is divided into four sections, each presenting the results of a team of international researchers, tackling the issue from a global, macroeconomic, and microeconomic approach. The first part examines the determinants of sustainable development in the global economy, while the second looks at enterprise in a sustainable world. The third section analyses the financial markets and the fourth addresses economic policy and sustainable development. A wide array of sustainability concerns are discussed in-depth, from analysing changes in environmental social, and governance reporting and assessing their impact on the information systems and reporting of economic entities; exploring the transition to 'Industry 5.0', and how technological innovation can be deployed to support a better fit and 'win-win' interaction between industry and society, shifting focus from economic and technological factors to important environmental and social dimensions. The monograph is an invaluable resource for scholars, researchers, and students of applied, development, growth, resource, and welfare economics. The policy recommendations will be of benefit to policymakers concerned with issues of sustainable development generally and the Sustainable Development Goals specifically.
Keywords: Sustainable development.; Environmental policy.; Social change -- Environmental aspects.; elektronické knihy; electronic books